Mask making get started in a new craft with easy-to-follow projects for beginners - Dickinson, Gill (Edison, N.J. : Chartwell Books, 1995)
Learn the art of mask making which has an on-going appeal for thousands of years. Be it for carneval or any other occasion, by creating your own original designs with paper, card boards, or natural materials from the woods, you will impress your friends and family.
Introduction - Materials and Techniques - Seaside shades - half-mask - lion mask - medusa mask - woodland half-mask - Panda - Feathered half-mask - Santa Claus - Witch - Punk - Monster Mask - Templates
Keywords: Masks; Handicraft